Building Ontology Based—0n Heterogeneous Data / Ta Duy Cong Chien, Phan Thi Tuoi - Ta Duy Cong Chien
In this paper. a domain Speciﬁc ontology called Information Technology Ontology (ITO) isproposed. This ontology is built basing on three distinct sources of Wikipedia, WordNet and ACMDigital Library. An information extraction system focusing on computing domain based on this on-tology in the future will be built. In order to have an ontology with highest quality and performanceas expected, the authors combine some algorithms between machine learning and natural languageprocessing (NLP) for building ontology.